ESSENTIAL CHARACTERISTICS OF THE DEVELOPMENT OF THE ENTERPRISE - LUKIANOVA, Valentyna; KHLIVNENKO, Maksym (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article is devoted to the study of the essential characteristics of the development of socio-economic systems in general and the enterprise, in particular. Attention is focused on the dependence of the perception of development and economic conditions in the country's economic system. A philosophical approach to the "development" category is presented. Because of the research of the views of domestic scientists, emphasis is placed on the main such feature as objective changes in the qualitative characteristics of the system. At the same time, three main directions of changes are highlighted - quantitative, structural and qualitative - which are clearly correlated. Other approaches to the concept of "development of the enterprise" are considered, which accordingly focus on: its acquisition of new opportunities and properties, qualities and characteristic features; quantitative changes in the system due to the process of transition to a new, higher quality state. The results of the study of various approaches of domestic scientists and their generalization made it possible to single out four differentiated groups of views on the economic context of the concept of "enterprise development", which are structured in the form of a table. A separate aspect of the consideration of this article is the main laws of the development of the economic system, on which the concept of enterprise development is based. These are the laws of unity of analysis and synthesis, development, stability, synergy, awareness, composition and proportionality. Based on the analysis of synonymous concepts, such as "organizational development" and "organizational development of the enterprise" and others, three main aspects of development are emphasized: scientific and technical, market and organizational. The importance of managing the development of the enterprise as a cyclical process of managing qualitative and quantitative changes in the organization with appropriate information support aimed at increasing the efficiency of the enterprise in the long term is emphasized. It was concluded that development is an integral process of the existence of any socio-economic systems and requires constant control and management by management.
Keywords: development; enterprise development; development laws; organizational development; enterprise development management